The costs of tax havens: Evidence from industry-level data - Petr Janský (Charles University in Prague, Institute of Economic Studies (IES), 2019)
Multinational enterprises make use of tax havens to avoid paying corporate income taxes and this costs hundreds billion USD in lost government revenue worldwide according to an increasing number of recent studies. None of those studies assigns these costs to industries. I aim to shed more light on this gap by using some of the best available industry-level US data to determine to what extent the location of the MNEs' profit is aligned with the location of their economic activities. My first finding is that the most important tax havens for US multinational enterprises are the Netherlands, Ireland and Luxembourg (all EU member states). Second, I systematically identify the specific industries in specific tax havens responsible for the costs, which should be useful information for tax authorities aiming to reduce tax avoidance. Finally, I argue that the current data are not detailed enough to provide a reliable industry breakdown of the costs, but the prospect of combining input-output tables with forthcoming country-by-country data seems more promising.
Keywords: F21; F23; H25; H26; H87; 330; Multinational enterprises; foreign direct investment; tax havens; industry-level data